Adsorptive removal of methylene blue by agar: effects of NaCl and ethanol - Samiey, Babak (BioMed Central, 2012)
Adsorption of methylene blue (MB) on agar was investigated as a function of temperature (308-328 K), different concentrations of NaCl and HCl and various weight percentages of binary mixtures of ethanol with water. It was observed that the maximum experimental adsorption capacity, q(m, exp), in water is up to 50 mg g(-1 )and decreases with increase in weight percentage of ethanol and NaCl and HCl concentration compared to that of water. Analysis of data using ARIAN model showed that MB adsorbs as monomer and dimer on the surface of agar. Binding constants of MB to agar were calculated using the Temkin isotherm. The process is exothermic in water and other solutions. The mean adsorption energy (E) value indicated binding of MB to agar is chemical adsorption. Kinetics of this interaction obeys from the pseudo-second-order model and diffusion of the MB molecules into the agar is the main rate-controlling step.